G.M. BRUÑO SAN MIGUEL FEBRES CORDERO The Christian Brother of scholar texts - Ocampo López, Javier (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The main goal of this text is the study about life. The Christian brother`s thought and action G.M. Bruño, San Miguel Febres Cordero. He is one of the scholar texts authors with the highest influence on Latin America at the end of century XIX and in the first half of XX. Arimetic, Algebra and geometrics texts from Christian Brother G.M. Bruño are remembered; those texts created Colombian and Ecuatorian people and others from other Latin American countries. He wrote more that fifty texts in Spanish and Literature, Spelling, Physics, Botany, Religion, Sacred History, Logarithm Chart, Accounting among others. The collection texts from G.M. Bruño is one of the most diverse and of importance in the Latin America Textology.